2022
DOI: 10.3390/molecules27061916
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenes against COVID-19: Repurposing C60 and C70 to Clog the Active Site of SARS-CoV-2 Protease

Abstract: The persistency of COVID-19 in the world and the continuous rise of its variants demand new treatments to complement vaccines. Computational chemistry can assist in the identification of moieties able to lead to new drugs to fight the disease. Fullerenes and carbon nanomaterials can interact with proteins and are considered promising antiviral agents. Here, we propose the possibility to repurpose fullerenes to clog the active site of the SARS-CoV-2 protease, Mpro. Through the use of docking, molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…In similar studies Calvaresi et al [59a] . determined that the core of C 60 occludes the enzyme cavity and interacts directly with the catalytic residue H41 by π‐π stacking interactions.…”
Section: Resultsmentioning
confidence: 88%
“…In similar studies Calvaresi et al [59a] . determined that the core of C 60 occludes the enzyme cavity and interacts directly with the catalytic residue H41 by π‐π stacking interactions.…”
Section: Resultsmentioning
confidence: 88%
“…Note that the unmodified C 60 fullerene molecule, which is highly lipophilic, according to experimental evidence presents an octanol-water partition coefficient of about 6.67 [ 55 ]. Unfortunately, since dendro[60]fullerene joined with molnupiravir is studied here for the first time, more focused comparisons with other relevant available studies [ 28 , 35 , 37 , 41 , 42 , 43 , 44 , 45 ] are not possible for the time being.…”
Section: Resultsmentioning
confidence: 99%
“…In order to reach clear conclusions, the dendro[60]fullerene alone is also tested in water and n-octanol environments to be compared with the proposed dendro[60]fullerene/molnupiravir molecules drug delivery system. Despite the fact that there are several reports [ 28 , 35 , 37 , 41 , 42 , 43 , 44 , 45 ] on the exploitation of the use of C 60 -based molecular systems against COVID-19, to the author’s best knowledge, this is the first time that dendro[60]fullerene has been proposed and tested as a possible nanovehicle of molnupiravir.…”
Section: Introductionmentioning
confidence: 99%
“…A few theoretical studies were carried out using density functional theory [ 65 ], docking and molecular dynamics [ 66 ], and energy decomposition techniques [ 67 ] to check the feasibility of using fullerene for inhibiting the coronavirus. The results revealed that, because of its hydrophobicity and stiffness, fullerene could minimize the factors that often oppose its binding with the SARS-CoV-2 virus, which makes fullerenes an excellent inhibitor.…”
Section: Applications Of Carbon Nanomaterials Against Covid-19mentioning
confidence: 99%